The importance of supervisor support to improve employee performance and retention in 5-star hotels in Bali - Astawa, I Ketut; Ek Armoni, Ni Luh; Putri Suardani, Anak Agung (Technium Social Sciences Journal, 2023)
The purpose of this research is to analyze the importance of supervisor support in motivating the work of operational employees and its implications for employee performance and retention in 5-star hotels in Bali. The problem in this research is how important supervisor support is in improving employee performance and retention and what the implications are. The population of this study was all permanent employees of 5-star hotels in Bali. A sampling of 5-star hotels used sampling areas, namely in Badung and Gianyar Regencies. The number of research respondents was 125 people, determined by purposive sampling. Data collection techniques through observation, interviews, and research questionnaires. Quantitative descriptive analysis is used to see the current condition of supervisors based on supervisor support, work motivation, performance, and employee retention so that it is known the importance of supervisor support in improving the performance and retention of 5-star hotel employees in Bali in the future. The results showed that supervisors’ support increased employee performance and retention with an average value in the interval 4.21-5.00. This means that supervisors support employee motivation, which affects high employee performance and retention.